Book Reviews (Journal of Finance, 1994)
Book reviewed in this article: Foundations of Financial Markets and Institutions . By FRANK J. FABOZZI, FRANCO MODIGLIANI, and MICHAEL G. FERRI. Economic Analysis of Investment Projects: A Practical Approach . By KEDAR N. KOHLI. The Armchair Economist: Economics and Everyday Life . By STEVEN E. LANDSBURG. Lost Prophets: An Insider's History of the Modern Economists . By ALFRED L. MALABRE, JR. A Contrarian Strategy for Growth Stock Investing: Theoretical Foundations and Empirical Evidence . By DONALD J. PETERS. Comeback: The Restoration of American Banking Power in the New World Economy . By ROY C. SMITH.